Polyphenols rich fraction from Geoffroea decorticans fruits flour affects key enzymes involved in metabolic syndrome, oxidative stress and inflammatory process - Costamagna, Milena Soledad (2015)
Geoffroea decorticans (chañar), is widely distributed throughout Northwestern Argentina. Its fruit is consumed as flour, arrope or hydroalcoholic beverage. The chañar fruits flour was obtained and 39 phenolic compounds were tentatively identified by HPLC-MS/MSn. The compounds comprised caffeic acid glycosides, simple phenolics (protocatechuic acid and vanillic acid), a glycoside of vanillic acid, p-coumaric acid and its phenethyl ester as well as free and glycosylated flavonoids. The polyphenols enriched extract with and without gastroduodenal digestion inhibited enzymes associated with metabolic syndrome, including -amylase, α-glucosidase, lipase and hydroxyl methyl glutaryl CoA reductase. The polyphenolic extract exhibited antioxidant activity by different mechanisms and inhibited the pro-inflammatory enzymes (ciclooxygenase, lipooxygenase and phospholipase A2). The polyphenolic extract did not showed mutagenic effect by Ames test against Salmonella typhimurium TA98 and TA100 strains. These findings add evidence that chañar fruit flour may be considered a functional food with preventive properties against diseases associated with oxidative stress, inflammatory mediators and metabolic syndrome.